BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Light and prey influence the abundances of two rhodopsins in the dinoflagellate Oxyrrhis marina - Martin Westermann; Christian Hoischen; Lars Wöhlbrand; Ralf Rabus; Erhard Rhiel (Protoplasma, 2023)
Antisera were raised against the C-terminal amino acid sequences of the two rhodopsins ADY17806 and AEA49880 of Oxyrrhis marina . The antisera and affinity-purified antibodies thereof were used in western immunoblotting experiments of total cell protein fractions from cultures grown either in darkness or in white, red, green, or blue light. Furthermore, the rhodopsin abundances were profiled in cultures fed with yeast or the prasinophyte Pyramimonas grossii . The immunosignals of ADY17806 and AEA49880 were similar when O. marina was grown in white, green, or blue light. Signal intensities were lower under conditions of red light and lowest in darkness. Higher amounts were registered for both rhodopsins when O. marina was fed with yeast compared to P. grossii . Furthermore, total cell protein of cultures of O. marina grown under all cultivation conditions was separated by sodium dodecyl sulfate polyacrylamide gel electrophoresis, followed by tryptic in-gel digestion and mass spectrometric analysis of the 25-kDa protein bands. The rhodopsin ADY17809 was detected in all samples of the light quality experiments and in 14 of the 16 samples of the prey quality experiments. The rhodopsin ABV22427 was not detected in one sample of the light quality experiments. It was detected in 15 of the 16 samples of the prey quality experiments. Peptide fragments of the other rhodopsins were detected less often, and no clear distribution pattern was evident with respect to the applied light quality or offered prey, indicating that none of them was exclusively formed under a distinct light regime or when feeding on yeast or the prasinophyte. Fluorescence light microscopy using the affinity-purified antibodies revealed significant labeling of the cell periphery and cell internal structures, which resembled vacuoles, tiny vesicles, and rather compact structures. Immunolabeling electron microscopy strengthened these results and showed that the cytoplasmic membrane, putative lysosome membranes, membranes encircling the food vacuole, and birefringent bodies became labeled.

Rhodopsins build up the birefringent bodies of the dinoflagellate Oxyrrhis marina - Erhard Rhiel; Christian Hoischen; Martin Westermann (Protoplasma, 2022)
The ultrastructure of the birefringent bodies of the dinoflagellate Oxyrrhis marina was investigated by transmission electron microscopy. Ultrathin sectioning revealed that the bodies consist of highly ordered and densely packed lamellae, which show a regular striation along their longitudinal axis. A lattice distance of 6.1 nm was measured for the densely packed lamellae by FFT (Fast Fourier Transformation) analysis. In addition, a rather faint and oblique running striation was registered. Lamellae sectioned rather oblique or almost close to the surface show a honeycombed structure with a periodicity of 7.2–7.8 nm. Freeze-fracture transmission electron microscopy revealed that the lamellae are composed of highly ordered, crystalline arrays of particles. Here, FFT analysis resulted in lattice distances of 7.0–7.6 nm. Freeze-fracture transmission electron microscopy further revealed that the bodies remained intact after cell rupture followed by ascending flotation of the membrane fractions on discontinuous sucrose gradients. The birefringent bodies most likely are formed by evaginations of membranes, which separate the cytoplasm from the food vacuoles. Distinct, slightly reddish-colored areas, which resembled the birefringent bodies with respect to size and morphology, were registered by bright field light microscopy within Oxyrrhis marina cells. An absorbance maximum at 540 nm was registered for these areas, indicating that they are composed of rhodopsins. This was finally proven by immuno-transmission electron microscopy, as antisera directed against the C-terminal amino acid sequences of the rhodopsins AEA49880 and ADY17806 intensely immunolabeled the birefringent bodies of Oxyrrhis marina .

Correction to: The proteorhodopsins of the dinoflagellate Oxyrrhis marina: ultrastructure and localization by immunofluorescence light microscopy and immunoelectron microscopy - Erhard Rhiel; Martin Westermann; Frank Steiniger; Christian Hoischen (Protoplasma, 2021)

The proteorhodopsins of the dinoflagellate Oxyrrhis marina: ultrastructure and localization by immunofluorescence light microscopy and immunoelectron microscopy - Erhard Rhiel; Martin Westermann; Frank Steiniger; Christian Hoischen (Protoplasma, 2020)
At least 7 proteorhodopsin sequences of Oxyrrhis marina were recently proven in bands obtained by sucrose density gradient centrifugation, and MS analyses revealed that the bands consisted almost of pure, native proteorhodopsins (Rhiel et al. 2020). The proteorhodopsin fractions, i.e., bands B2, B3, and B4 were subjected to transmission electron microscopy. Negative staining revealed that band B2 consisted most likely of monomeric/oligomeric proteorhodopsins with particle dimensions of about 6 nm. Negative staining, freeze-fracture, and cryo-transmission electron microscopy revealed that bands B3 and B4 consisted of vesicular, sheet-like, and cup-shaped structures which all seemed to be composed of protein. Frequently, ring-like protein aggregates were registered at higher magnifications. They measured about 4 nm in diameter with a tiny hole of 1.5 nm in the middle. The bands B2, B3, and B4 were pooled and used to raise an antiserum. Immunoelectron microscopy resulted in intense labeling of the isolated structures. Immunofluorescence light microscopy of formaldehyde-fixed Oxyrrhis cells resulted in intense labeling of the cell periphery. Some cell internal structures became labeled, too. Immunoelectron microscopy of freeze-fractured cells revealed that most likely the membranes of the amphiesmal vesicles were labeled at the cell periphery, while the cell internal label seemed to originate from the food vacuoles.

Toxicological assessment of magnesium oxide nanoparticles in HT29 intestinal cells - Anna Mittag; Thomas Schneider; Martin Westermann; Michael Glei (Archives of Toxicology, 2019)

The different morphologies of yeast and filamentous fungi trigger distinct killing and feeding mechanisms in a fungivorous amoeba - Silvia Radosa; Iuliia Ferling; Jakob L. Sprague; Martin Westermann; Falk Hillmann (Environmental Microbiology, 2019)
Summary Size and diverse morphologies pose a primary challenge for phagocytes such as innate immune cells and predatory amoebae when encountering fungal prey. Although filamentous fungi can escape phagocytic killing by pure physical constraints, unicellular spores and yeasts can mask molecular surface patterns or arrest phagocytic processing. Here, we show that the fungivorous amoeba Protostelium aurantium was able to adjust its killing and feeding mechanisms to these different cell shapes. Yeast‐like fungi from the major fungal groups of basidiomycetes and ascomycetes were readily internalized by phagocytosis, except for the human pathogen Candida albicans whose mannoprotein coat was essential to escape recognition by the amoeba. Dormant spores of the filamentous fungus Aspergillus fumigatus also remained unrecognized, but swelling and the onset of germination induced internalization and intracellular killing by the amoeba. Mature hyphae of A. fumigatus were mostly attacked from the hyphal tip and killed by an actin‐mediated invasion of fungal filaments. Our results demonstrate that predatory pressure imposed by amoebae in natural environments selects for distinct survival strategies in yeast and filamentous fungi but commonly targets the fungal cell wall as a crucial molecular pattern associated to prey and pathogens.

In vitro uptake and toxicity studies of metal nanoparticles and metal oxide nanoparticles in human HT29 cells - Thomas Schneider; Martin Westermann; Michael Glei (Archives of Toxicology, 2017)

Virulence determinants of the human pathogenic fungus A spergillus fumigatus protect against soil amoeba predation - Falk Hillmann; Silvia Novohradská; Derek J. Mattern; Tilmann Forberger; Thorsten Heinekamp; Martin Westermann; Thomas Winckler; Axel A. Brakhage (Environmental Microbiology, 2015)
Summary Filamentous fungi represent classical examples for environmentally acquired human pathogens whose major virulence mechanisms are likely to have emerged long before the appearance of innate immune systems. In natural habitats, amoeba predation could impose a major selection pressure towards the acquisition of virulence attributes. To test this hypothesis, we exploited the amoeba Dictyostelium discoideum to study its interaction with A spergillus fumigatus , two abundant soil inhabitants for which we found co‐occurrence in various sites. Fungal conidia were efficiently taken up by D . discoideum , but ingestion was higher when conidia were devoid of the green fungal spore pigment dihydroxynaphtalene melanin, in line with earlier results obtained for immune cells. Conidia were able to survive phagocytic processing, and intracellular germination was initiated only after several hours of co‐incubation which eventually led to a lethal disruption of the host cell. Besides phagocytic interactions, both amoeba and fungus secreted cross inhibitory factors which suppressed fungal growth or induced amoeba aggregation with subsequent cell lysis, respectively. On the fungal side, we identified gliotoxin as the major fungal factor killing D ictyostelium , supporting the idea that major virulence attributes, such as escape from phagocytosis and the secretion of mycotoxins are beneficial to escape from environmental predators.

Isolation and characterisation of the trichocysts of the dinophyte Prorocentrum micans - Martin Westermann; Frank Steiniger; Nils Gülzow; Helmut Hillebrand; Erhard Rhiel (Protoplasma, 2015)

Isolation and characterization of the ejectisomes of the prasinophyte Pyramimonas grossii - Erhard Rhiel; Martin Westermann; Frank Steiniger; Christian Kirchhoff (Protoplasma, 2013)

Ejectisins: tough and tiny polypeptides are a major component of cryptophycean ejectisomes - Silke Ammermann; Tristan Schneider; Martin Westermann; Helmut Hillebrand; Erhard Rhiel (Protoplasma, 2013)

Influence of (S)-ketamine on human motor cortex excitability - Oliver Höffken; Ida S. Haussleiter; Andrea Westermann; Jörn Lötsch; Christoph Maier; Martin Tegenthoff; Peter Schwenkreis (Experimental Brain Research, 2013)

Proteinase-activated receptor 2 (PAR2) in cholangiocarcinoma (CCA) cells: effects on signaling and cellular level - Roland Kaufmann; Alexander Hascher; Franziska Mußbach; Petra Henklein; Kathrin Katenkamp; Martin Westermann; Utz Settmacher (Histochemistry and Cell Biology, 2012)

Ultrastructural freeze-fracture immunolabeling identifies plasma membrane-localized syndapin II as a crucial factor in shaping caveolae - Dennis Koch; Martin Westermann; Michael M. Kessels; Britta Qualmann (Histochemistry and Cell Biology, 2012)

Isolation, purification and some ultrastructural details of discharged ejectisomes of cryptophytes - Erhard Rhiel; Martin Westermann (Protoplasma, 2012)

The shape of caveolae is omega-like after glutaraldehyde fixation and cup-like after cryofixation - Wiebke Schlörmann; Frank Steiniger; Walter Richter; Roland Kaufmann; Gerd Hause; Cornelius Lemke; Martin Westermann (Histochemistry and Cell Biology, 2010)

Improved antigen retrieval in freeze-fracture cytochemistry by evaporation of carbon as first replication layer - Wiebke Schlörmann; Markus John; Frank Steiniger; Martin Westermann; Walter Richter (Histochemistry and Cell Biology, 2007)

Growth substrate dependent localization of tetrachloroethene reductive dehalogenase in Sulfurospirillum multivorans - Markus John; Roland P. H. Schmitz; Martin Westermann; Walter Richter; Gabriele Diekert (Archives of Microbiology, 2006)

Belt-like localisation of caveolin in deep caveolae and its re-distribution after cholesterol depletion - Martin Westermann; Frank Steiniger; Walter Richter (Histochemistry and Cell Biology, 2005)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

A new type of complementary chromatic adaptation exemplified byPhormidium sp. C86: Changes in the number of peripheral rods and in the stoichiometry of core complexes in phycobilisomes - Martin Westermann; Werner Wehrmeyer (Archives of Microbiology, 1995)

A new type of complementary chromatic adaptation exemplified by Phormidium sp. C86: changes in the number of peripheral rods and in the stoichiometry of core complexes in phycobilisomes - Martin Westermann; W. Wehrmeyer (Archives of Microbiology, 1995)

Ultrastructure of cell wall and photosynthetic apparatus of the phycobilisome-less - Martin Westermann; Anneliese Ernst; Susanne Brass; Peter Böger; W. Wehrmeyer (Archives of Microbiology, 1994)